Effects of a low‐viscosity lower crust on topography and gravity at convergent mountain belts during gravitational instability of mantle lithosphere. Issue 1 (12th January 2015) - Molnar, Peter; Houseman, Gregory A.
Abstract We examine the gravitational stability of a stratified structure consisting of a low‐density crust through which viscosity decreases exponentially, over a denser mantle lithosphere of constant viscosity, which in turn overlies an inviscid, slightly less dense layer like the asthenosphere. The most important aspect of the viscosity structure is the contrast in viscosity at the Moho. Surface uplift above a mantle downwelling is greatest when the viscosity contrast at the Moho is negligible. The surface is depressed when the viscosity of the lowermost crust is much greater than mantle viscosity. For a wide range of viscosity structures, calculated gravity anomalies and in particular admittances (ratios of the Fourier transform of gravity to that of topography) produced by Rayleigh‐Taylor instability differ markedly from those observed across convergent mountain belts. In particular, whereas values of calculated admittance are negative, or very small, observed admittances are consistently positive. Thus, if downwelling of mantle lithosphere directly beneath mountain ranges plays an important role in the construction of mountain belts, it cannot be the main process that induces crustal thickening.